Pemanfaatan Video Animasi dan Kuis Teka-Teki Silang dalam Pembelajaran Matematika - Novita Fatmiyati; Jasmine Salsabila Lutfi; Mursidah Mursidah; Intan Susilawati; Nanang Priatna; Sumanang Muhtar Gozali (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
The dedication activities in SD Negeri Cihanjuang 2 aimed to introduce students to animated learning videos they did not get before in class. Animation-based learning video contains whole-number four basic arithmetic operations consisting of addition, subtraction, multiplication, and division operations. In addition, the activity also used the evaluation of Crossword Puzzle quizzes and images they commonly find in everyday life to help students visualize abstract mathematical problems. The target of this activity is students-class VI SD Negeri Cihanjuang 2, which has 23 students. The six stages carried out in this activity, namely the preparation stage, group division stage, delivery of material through animation-based video learning and emphasis on the concept of whole-number operations stage, giving the Crossword Puzzle quizzes stage, discussion stage, and evaluation stage. Based on the observations, many students showed interest and positive responses in listening and paying attention to learning videos and actively asking and discussing during solving quizzes and discussing topics.